Tamsulosin in Lowering Double J Related Symptoms - KC, Sudeep Raj; Timilsina, Bhusan Raj; Devkota, Gaurav; Shah, Rajiv; Lamichhane, Nirmal (Journal of College of Medical Sciences-Nepal, 2018)
Background: Indwelling double J ureteral stents are used routinely in the resolution of ureteral obstruction caused by different etiologies. Evaluation of urinary symptoms related to double-J stent indicate that these affect 73-90% of patients. Aim of this study is to evaluate the effect of tamsulosin on the DJ related complications to improve the quality of life and render symptom free life. Material and Methods: Quasi experimental study was carried out in the department of urology in College of Medical Science, teaching hospital Chitwan, Nepal from 15th March 2017 to 15th March 2018. A total of 80 post operative patients were included in this study and were randomized into Group A and B with 40 patient in each group. Stent related symptoms, quality of life and IPSS (International prostate symptom score) were evaluated at the time of discharge and at the time of DJ removal. Pain was evaluated with the help of VAS at the time of discharge and at the time of DJ removal. Data were entered in MS-Excel and were imported to EZR software Version 3.4.1 for analysis. A p-value of less than 0.05 was considered significant. Results: Median age was 30.5 in Tamsulosingroup and24years in placebo group. (p=0.68).At the time of discharge significant difference was noted in IPSS (p<0.001), butno significant difference wasnoted with QoL index (p=0.932) and VAS (p=0.68). At the time of DJ stent removal, significant difference was noted with IPSS (p<0.001), QoL index (p<0.001), VAS (p=0.004) in Tamsulosin group than in Placebo group. Conclusion: Tamsulosin lowers stent related symptoms, pain and improves quality of life in patientswith indwelling DJ stent. Key words: DJ stent; IPSS; Tamsulosin; VAS.